1984
DOI: 10.1139/v84-331
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of (+)-aphidicol-15-ene

Abstract: A stereospecific synthesis of (+)-aphidicol-15-ene is described. Pursuing a concept successfully applied to our total synthesis of stemarin and the stemodane diterpenoids, the C/D ring system was elaborated by functional group manipulation and rearrangement of a 6-hydroxybicyclo[2.2.2]octan-2-one system. RONALD B. KELLY, G. SANKAR LAL, GOPALA GOWDA et RABINDRA N. Rw. Can. J. Chem. 62, 1930Chem. 62, (1984. This concept was an efficient feature of total syntheses of stemarin (1)(1), and of 2-desoxystemodinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…(+)-Podocarpic acid (4) was then used for obtaining (+)-stemod-12-ene (31) and (+)-2-deoxystemodinone (2d), thus confirming the absolute configuration attributed to the stemodane diterpenoids on the basis of ORD and CD studies [50]. (+)-Podocarpic acid (4) was also converted into (+)-aphidicol-15-ene (36) [51] and into the Stemodia chilensis tetracyclic diterpenoid (+)-19-acetoxystemodan-12-ol (2f) allowing confirmation of the structure attributed to the latter only on the basis of NMR experiments [54]. (+)-Podocarpic acid (4) was then extensively used in the work which led to the synthesis of (+)-stemar-13-ene (57) and (+)-18-deoxystemarin (3b) [55,56,59,60,62].…”
Section: Synthesis Of (+)-Stemar-13-enementioning
confidence: 62%
See 2 more Smart Citations
“…(+)-Podocarpic acid (4) was then used for obtaining (+)-stemod-12-ene (31) and (+)-2-deoxystemodinone (2d), thus confirming the absolute configuration attributed to the stemodane diterpenoids on the basis of ORD and CD studies [50]. (+)-Podocarpic acid (4) was also converted into (+)-aphidicol-15-ene (36) [51] and into the Stemodia chilensis tetracyclic diterpenoid (+)-19-acetoxystemodan-12-ol (2f) allowing confirmation of the structure attributed to the latter only on the basis of NMR experiments [54]. (+)-Podocarpic acid (4) was then extensively used in the work which led to the synthesis of (+)-stemar-13-ene (57) and (+)-18-deoxystemarin (3b) [55,56,59,60,62].…”
Section: Synthesis Of (+)-Stemar-13-enementioning
confidence: 62%
“…Reduction of the latter with tri-n-butyltin hydride followed by saponification gave 47. The conversion of 47 into (+)-36 [51] paralleled that of 42a into (+)-31 [50] (see Section 8.4). …”
Section: Synthesis Of (+)-Aphidicol-15-ene (1984)mentioning
confidence: 93%
See 1 more Smart Citation
“…This goal was achieved by locating, in a substituted bicyclo[2.2.2]octane system, at a specific position, a suitably configurated leaving group the departure of which promoted the migration of the antiperiplanar C-C bond. Remarkable examples of such specificity were reported in the past in the frame of biogenetic syntheses of stemodane [4,5,9,[29][30][31][32][33], aphidicolane [30,31,[34][35][36][37][38] and stemarane [39][40][41][42][43][44], diterpenes and diterpenoids. As can be seen (Scheme 4), the bonds indicated by a green arrow migrate in one case (entry a) through the lower face of the molecule, while in entry b, the same bond migrates through the lower face owing to the different location of the leaving group.…”
Section: Biogenesismentioning
confidence: 99%
“…[1], there are only 5 more recent studies on pore etching [2 -5] and no macropores were found so far by pure anodic etching. While Ge today plays only a marginal role in semiconductor technology, pore formation in Ge could be of interest for applications like photonic crystals [6], sensors or filters. In this letter anodically etched Ge macropores and their morphological features are reported for the first time.…”
mentioning
confidence: 99%